2015
DOI: 10.1016/j.apmr.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation Among Individuals With Dysvascular Lower Extremity Amputation

Abstract: SI was common among those with recent LEA. Several aspects of an amputee's clinical presentation, such as physical functioning, satisfaction with functioning, and self-efficacy, were associated with SI, although depression severity was the best risk marker. A subset of the sample endorsed SI in the absence of a positive depression screen. Brief screening for depression that includes assessment of SI is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 82 publications
0
11
0
1
Order By: Relevance
“…Further, amputations and other associated disabilities were found to be associated with suicidal ideations ( Turner et al, 2015 ). The study by Turner et al (2015) concluded that suicidal ideations are common among those with recent amputations and nurses as well as other health team members ought to recognize this increased risk to prevent suicide.…”
Section: Acute and Chronic Health Challenges With Suicidal Tendenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, amputations and other associated disabilities were found to be associated with suicidal ideations ( Turner et al, 2015 ). The study by Turner et al (2015) concluded that suicidal ideations are common among those with recent amputations and nurses as well as other health team members ought to recognize this increased risk to prevent suicide.…”
Section: Acute and Chronic Health Challenges With Suicidal Tendenciesmentioning
confidence: 99%
“…Further, amputations and other associated disabilities were found to be associated with suicidal ideations ( Turner et al, 2015 ). The study by Turner et al (2015) concluded that suicidal ideations are common among those with recent amputations and nurses as well as other health team members ought to recognize this increased risk to prevent suicide. Also, suicide has been found to be higher among adults with disabilities compared to their counterparts without disabilities, and suicide is mostly preceded with suicidal ideations ( Shim and Hahm, 2011 ; Acheampong and Aziato, 2018 ).…”
Section: Acute and Chronic Health Challenges With Suicidal Tendenciesmentioning
confidence: 99%
“…Among patients with PAD, the prevalence of depression ranges from 16% 28 to 46%. 29 PAD is associated with impaired quality of life, 30 which may increase the incidence of depression.…”
Section: Evidence Linking Pad and Depressionmentioning
confidence: 99%
“…116 In a separate study of patients who underwent lower extremity amputations for complications related to diabetes mellitus or PAD, there was a 16% prevalence of suicidal ideation at 1 year, which was significantly associated with lower levels of mobility and activities of daily living independence. 28…”
Section: Impact Of Depression On Pad Outcomesmentioning
confidence: 99%
“…The high rate of 1-year mortality is usually from associated stroke or myocardial infarction (MI) 11 - 15 . Studies investigating health-related quality of life (QoL) in patients with PVD have revealed that QoL is primarily determined by mobility impairment 16 , 17 . Therefore, restoring functional mobility may provide substantial benefit to these amputees 18 .…”
mentioning
confidence: 99%